PENGARUH FAKTOR GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN - Nurbaety; Munandar, Agus (Jurnal Riset Terapan Akuntansi, 2025)
This study evaluates the influence of several factors on the profitability of consumer goods and agricultural industry companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The dependent variable is profitability, while the independent variables include controlling shareholders, foreign ownership, board of directors, size of the independent board of commissioners, and institutional ownership. Profitability is an important indicator of corporate performance, reflecting the ability to generate profit from operations. The study employs a quantitative approach and panel data in the form of annual financial statements accessed through the official IDX website. The sampling technique used is purposive sampling, while the analytical method applied is panel data regression, combining cross-section and time-series data. Data were processed using Stata and SPSS. Stata was used to test the Common Effect Model, Fixed Effect Model, and Random Effect Model, with results indicating the Fixed Effect Model (FEM) as the best fit. SPSS was further used for Normality, Autocorrelation, Heteroscedasticity, Multicollinearity, t-test, F-test, and Coefficient of Determination (R2). The t-test shows that controlling shareholders significantly influence profitability, while foreign ownership, independent commissioners’ size, and institutional ownership have no significant effect. This research provides management and investors with insights for strategic decision-making. Keywords: profitability, foreign ownership, directors.